2017
DOI: 10.15694/mep.2017.000154
|View full text |Cite
|
Sign up to set email alerts
|

Student-focused virtual histology education: Do new scenarios and digital technology matter?

Abstract: Innovative changes have become a critical part of teaching when resources are limited. In this study, we examined whether the studentoriented teaching method, when powered by virtual microscopy, improves histology learning compared to traditional microscope-based studies. Anonymous and voluntary post-course surveys were administered to students and essays were processed for content analysis. Google Analytics was used to obtain accurate Internet usage monitoring for WEBMICROSCOPE®. Using SPSS statistics, the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Academic gains seen in this study were consistent with knowledge building on Bloom's Taxonomy (Thomas and Storr, 2015). Gains at the knowledge level were the type of gains seen in Felszeghy et al's study (Felszeghy et al, 2017). In a different study, Benedict et al (2013) demonstrated students overwhelmingly supported self-directed learning (Benedict, Schonder and McGee, 2013).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Academic gains seen in this study were consistent with knowledge building on Bloom's Taxonomy (Thomas and Storr, 2015). Gains at the knowledge level were the type of gains seen in Felszeghy et al's study (Felszeghy et al, 2017). In a different study, Benedict et al (2013) demonstrated students overwhelmingly supported self-directed learning (Benedict, Schonder and McGee, 2013).…”
mentioning
confidence: 67%
“…A new, more effective and thought-evoking teaching program to medical and dental students was adopted in the Institute of Biomedicine, University of Eastern Finland, Kuopio, Finland in 2016. According to our study, histology learning and participation improved compared to traditional microscope-based teaching when virtual microscopy was combined with a student-centered approach (Felszeghy et al 2017). The following salient points from this article promote student engagement and learning: student centered learning, collaborative learning, peer-to-peer learning and peer-to-peer teaching (Felszeghy et al 2019).…”
mentioning
confidence: 77%
See 3 more Smart Citations